PENGARUH WORK OVERLOAD DAN WORK FAMILY CONFLICT TERHADAP TURNOVER INTENTION YANG DIMEDIASI OLEH WORK EXHAUSTION - Nisa, Nurul Hidayatin; Malik, Nazaruddin (Faculty of Economics and Business, University of Muhammadiyah Malang, 2016)
The purpose of this research was to examine factors that determine turnover intention in medical representative at PT. APL. To be known before that medical representatives have high percentage in turnover. The research using work exhaustion as mediation to determine the relationship between works overload and work family conflict of turnover intention. Research method is quantitative approach in causal research. The analysis tools are AMOS and T-Sobel. Findings of this research are both work overload and work family conflict berpengaruh with work exhaustion and turnover intention, work exhaustion mediated work overload and work family conflict over turnover intention.